Service level manager careers in IT service management - Sansbury, John (BCS Learning & Development, 2017)
The role of service level manager is a critical one in that the agreements negotiated with customers should inform the activities of the service provider. This book aims to help those whose role is to establish, negotiate, manage or update service level agreements and to use these as the basis of continual service improvement. It covers areas such as purpose, required skills, responsibilities, interface and career progression as well as tools, standards and frameworks related to the role.
Includes bibliographical references and index. - Online resource; title from title page (Safari, viewed August 16, 2017)
Keywords: Information technology -- Management; Business -- Data processing -- Management; Service-level agreements; Technologie de l'information; Gestion; Gestion; Informatique; Gestion; Qualité de service; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; Business; Data processing; Management; Information technology; Management